СУТНІСТЬ ТА ЗНАЧЕННЯ ДЕРЖАВНО-ПРИВАТНОГО ПАРТНЕРСТВА У СФЕРІ ВИЩОЇ ОСВІТИ - Боднар, Сергій Вікторович (SUPREMANCE OF LAW, 2019)
In the article, based on the analysis of the scientific views of scientists and the norms of the current legislation, the author’s definition of the concept of public-private partnership in the field of higher education is proposed. The key aspects that most fully and meaningfully reveal the essence and purpose of public-private partnership in the field of higher education are highlighted.
Keywords: partnership; public-private partnership; sphere of higher education